Alleviation of cognitive deficits in a rat model of glutamate-induced excitotoxicity, using an N-type voltage-gated calcium channel ligand, extracted from Agelena labyrinthica crude venom - Keimasi, Mohammad; Salehifard, Kowsar; Keimasi, Mohammadjavad; Amirsadri, Mohammadreza; Esfahani, Noushin Mirshah Jafar; Moradmand, Majid; Esmaeili, Fariba; Mofid, Mohammad Reza (Frontiers in Molecular Neuroscience, 2023)
Excitotoxicity is a common pathological process in Alzheimer's disease (AD) which is caused by the over-activity of N-Methyl-D-Aspartate receptors (NMDARs). The release of neurotransmitters depends on the activity of voltage-gated calcium channels (VGCCs). Hyper-stimulation of NMDARs can enhance the releasement of neurotransmitters through the VGCCs. This malfunction of channels can be blocked by selective and potent N-type VGCCs ligand. Under excitotoxicity condition, glutamate has negative effects on the pyramidal cells of the hippocampus, which ends in synaptic loss and elimination of these cells. These events leads to learning and memory elimination through the hippocampus circuit's dysfunction. A suitable ligand has a high affinity to receptor or channel and is selective for its target. The bioactive small proteins of venom have these characteristics. Therefore, peptides and small proteins of animal venom are precious sources for pharmacological applications. The omega-agatoxin-Aa2a was purified, and identified from Agelena labyrinthica specimens, as an N-type VGCCs ligand for this study. The effect of the omega-agatoxin-Aa2a on the glutamate-induced excitotoxicity in rats was evaluated through behavioral tests including Morris Water Maze, and Passive avoidance. The syntaxin1A (SY1A), synaptotagmin1 (SYT1), and synaptophysin (SYN) genes expression were measured via Real-Time PCR. The local expression of synaptosomal-associated protein, 25k Da (SNAP-25) was visualized using an immunofluorescence assay for synaptic quantification. Electrophysiological amplitude of field excitatory postsynaptic potentials (fEPSPs) in the input–output and LTP curves of mossy fiber were recorded. The cresyl violet staining of hippocampus sections was performed for the groups. Our results demonstrated that the omega-agatoxin-Aa2a treatment could recover the learning, and memory impairment caused by NMDA-induced excitotoxicity in rat hippocampus.